Tuladha prasaja kagem panatacara tuwin pamedhar sabda Muh. Muslich H.S., Hariyoto ; penyunting, A. Choiran Marzuki. - MUSLICH H.S., Muh.; Hariyoto; Choiran Marzuki, A. (Mitra Pustaka, 2008)
xii, 128 hlm. 20 cm (3 eks.)